2022
DOI: 10.3847/1538-4357/ac723a
|View full text |Cite
|
Sign up to set email alerts
|

The 30 Doradus Molecular Cloud at 0.4 pc Resolution with the Atacama Large Millimeter/submillimeter Array: Physical Properties and the Boundedness of CO-emitting Structures

Abstract: We present results of a wide-field (approximately 60 × 90 pc) Atacama Large Millimeter/submillimeter Array mosaic of CO(2–1) and 13CO(2–1) emission from the molecular cloud associated with the 30 Doradus star-forming region in the Large Magellanic Cloud (LMC). Three main emission complexes, including two forming a bow-tie-shaped structure extending northeast and southwest from the central R136 cluster, are resolved into complex filamentary networks. Consistent with previous studies, we find that the central re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 63 publications
3
37
0
Order By: Relevance
“…This result suggests that the super star cluster R136 and in general the massive-star formation to the north are not strongly affecting the physical conditions in the Ridge at this distance. This is consistent with the findings of Wong et al (2022) that there is little correlation with α vir for clouds in 30 Dor and their distance to R136.…”
Section: Spatial Dependencesupporting
confidence: 92%
See 2 more Smart Citations
“…This result suggests that the super star cluster R136 and in general the massive-star formation to the north are not strongly affecting the physical conditions in the Ridge at this distance. This is consistent with the findings of Wong et al (2022) that there is little correlation with α vir for clouds in 30 Dor and their distance to R136.…”
Section: Spatial Dependencesupporting
confidence: 92%
“…This value of X 13CO is also consistent with using a typical galactic X CO factor of 2 × 10 20 cm −2 (K km s −1 ) −1 (Bolatto et al 2013) and a 13 CO (1-0)/ 12 CO (1-0) integrated intensity ratio of 0.12 (Finn et al 2021). The resulting column densities for 30 Dor also match the ranges of those calculated using LTE assumptions in Wong et al (2022).…”
Section: Derived Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…To overcome this obstacle, our mass estimation method takes place in two parts (described in this section and Section 2.1.3). Additionally, our mass estimation method is similar to the approach taken by Wong et al (2022), who, in their study of the LMC's 30 Doradus region, found that 53% of CO-detected clumps were only traced by 12 CO and did not have corresponding 13 CO emission. The majority of the clumps in N90 with corresponding 13 CO emission are located in the northeast rim and nonrim sections near NGC 602, with several others on the northwest rim near the massive O3 star Sk 183 (see definitions of these subregions in Figure 7(a)).…”
Section: Molecular Column Densitymentioning
confidence: 86%
“…Although the large-scale H I flow scenario was originally designed to explain the R136 formation (Fukui et al 2017), the fact that the same flow distributes over kiloparsec scales motivates us to apply it describing the star formation history in N159. In a reimportation of this context, an ALMA wide-field imaging study found an N159-type conical molecular filament system around R136 (Wong et al 2022). These observational pieces of evidence may demonstrate that galaxy-scale (H I) gas flows and the subsequent more than a few ×10 pc scale filament system development are universally responsible for the super star cluster formation that can drive galaxy evolution itself.…”
Section: Muraoka Et Al 2020mentioning
confidence: 96%